Managing media businesses : a game plan to navigate disruption and uncertainty - Rosenberg, Michael (Economist); Seager, Philip H. (Palgrave Macmillan, 2017)
This book is a practical guide to every aspect of managing media businesses. Written by a team of experts and illustrated with interviews from leading industry players, it addresses the unprecedented change and uncertainty facing the industry. Do newspapers, magazines or books have a future? Will terrestrial television or cable services exist as meaningful players in five years' time? Is there a way to make multiple consumption platforms work together in a way that extracts the revenue needed to support the creation and development of quality content? While more and more content is being published, fewer and fewer businesses are finding a way to do so profitably and sustainably. Your answers to these questions that vex your media or entertainment business will depend on your frame - a frame based on experience gained in days that were less uncertain, less fluid and much, much simpler. Those frames need to be broken if you are to survive in times of such rapid change. This book is based on IESE's Advanced Management Program in Media & Entertainment, which IESE Business School has been running in New York and Los Angeles since 2011. It combines contributions from leading professors and practitioners, as well as real-life case studies, to establish a base upon which you can start to build the set of managerial tools that you will need to manage fast-changing media and entertainment businesses.